Respuesta :

Answer:

3

Step-by-step explanation:

6(2x-3)=-(x-9)+4x (Distributive property)

12x-18=-x+9+4x

12x-4x+x=9+18 (Collecting like terms)

9x=27 (Division)

x=3

Hope I am correct :)

Answer:

3

Option D is the correct option.

Step-by-step explanation:

6 ( 2x - 3 ) = - ( X - 9 ) + 4x

Distribute 6 through the parantheses

12x - 18 = - ( X - 9) + 4x

When there is a (-) in front of an expression in parantheses, change the sign of each term in the expression

12x - 18 = -x + 9 + 4x

Collect like terms

12x - 18 = 3x + 9

Move variable to Left hand side and change its sign

12x - 3x - 18 = 9

Move constant to Right hand side and change its sign

12x - 3x = 9 + 18

collect like term

9x = 9 + 18

Add the numbers

9x = 27

Divide both sides of the equation by 9

9x /9 = 27/ 9

Calculate

X = 3

Hope this helps....

Good luck on your assignment...

ACCESS MORE